Total energy expenditure and the energy components for amenorrhoeic collegiate runners - Uchizawa, A.; Kondo, E.; Enomoto, Y.; Tokuyama, K.; Omi, N.; Sagayama, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
It is necessary to investigate energy requirements to establish energy intake strategies. However, few research has measured using doubly labeled water (DLW) method total energy expenditure (TEE) and physical activities under the free-living condition in female runners with amenorrhoea. This study aimed to investigate the TEE and the energy components of TEE for collegiate female runners with amenorrhoea. Six female middle- and long-distance runners with amenorrhea participated (20 ± 2 y). TEE and physical activity level (PAL) were determined using the DLW method for 1 week. Daily physical activity and energy intake (EI) were measured using tri-accelerometers and dietary record during the period, respectively. Measured resting energy expenditure (mREE) and sleeping metabolic rate (mSMR) was used for a metabolic chamber on the last day of the period. Exercise energy expenditure (EEE) was estimated by subtracting daily physical activity energy expenditure (DPAEE) and mREE from TEE. The running distance per week was reported based on training records and use-owned wearable technological devices by themselves. Energy availability (EA) was calculated by subtracting EEE from EI by dietary records. Estimated SMR (eSMR) and REE (eREE) were calculated using an estimation equation. The mean TEE, PAL, DPAEE, EEE, and the running distance were 2577 ± 208 kcal/day, 2.1 ± 0.3, 1052 ± 275 kcal/day, 893 ± 324 kcal/day, and 74.0 ± 23.5 km/week, respectably. EA was correlated with REE (r = 0.837, p < 0.05) and SMR (r = 0.842, p < 0.05). There was no difference between the estimated and measured energy expenditure in resting and sleeping. These values ratio were REE (mREE/eREE: 1.08 ± 0.08) and SMR (mSMR/eSMR: 0.98 ± 0.11). The relative components against TEE were 47.9% for mREE, 17.4% for DPAEE, and 34.6% for EEE. Our results may serve as a reference to help the adequate energy requirements for collegiate female runners with amenorrhea in determining their nutritional strategies.